2022
DOI: 10.3390/cells11203269
|View full text |Cite
|
Sign up to set email alerts
|

Key Genes Associated with Pyroptosis in Gout and Construction of a miRNA-mRNA Regulatory Network

Abstract: This study aimed to analyze key hub genes related to pyroptosis in gout and construct a miRNA-mRNA regulatory network using bioinformatic tools to elucidate the pathogenesis of gout and offer novel ideas to develop targeted therapeutic strategies for gout. Methods: The GSE160170 dataset was downloaded from the GEO database. The expression data extracted from the dataset were used to screen for differentially expressed genes (DEGs), which intersected with pyroptosis-related genes. These DEGs were analyzed via G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…The core targets of IL1B, 21 CXCL8, 22 , 23 and PTGS2 24 with the highest correlation with acute gout inflammation were analyzed and extracted, and the core small-molecule ligands (quercetin, emodin, rhein, etc.) were extracted from the PubChem and PDB databases.…”
Section: Resultsmentioning
confidence: 99%
“…The core targets of IL1B, 21 CXCL8, 22 , 23 and PTGS2 24 with the highest correlation with acute gout inflammation were analyzed and extracted, and the core small-molecule ligands (quercetin, emodin, rhein, etc.) were extracted from the PubChem and PDB databases.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic analyses revealed shared genetic bases for body mass index and gout, and adherence to a healthy diet was associated with a lower risk of gout in genetically susceptible female individuals (17,18). Epigenetic studies highlighted micro-RNAs that could influence gout development by regulating gene expression (19). An epigenome-wide association study identified specific CpG DNA sequences associated with SUA levels, providing insights into co-regulation and genetic effects on SUA levels, particularly in genes related to small molecule transport and cardiometabolic traits (20).…”
Section: Take-home Messagesmentioning
confidence: 99%